Itinerari danteschi nelle culture slave - Siedina, Giovanna (Biblioteca di Studi di Filologia Moderna, 2022)
A little more than 700 years after the death of the great Italian poet, this book intends to contribute to the assessment of what place the literary, cultural and linguistic heritage of the great Italian poet has had in linguistic development, in the formation of national consciousness of the Slavic peoples, in their literatures and in the elaboration of their literary canon, especially in the post-1991 period. Indeed, in the last thirty years, many political, social, cultural and linguistic changes have taken place in the varied panorama of the Slavic countries. New states have arisen, with their respective national languages and with the need to revise or elaborate their respective literary canons. The volume contains essays on Dante's reception in Belarus, Bulgaria, Czechia, Croatia, Macedonia, Poland, Russia, Serbia, Slovakia, and Ukraine.